2004
DOI: 10.1111/j.1348-0421.2004.tb03607.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Evidence Suggesting Clostridium difficile Is Present in Human Gut Microbiota More Frequently than Previously Suspected

Abstract: Prevalence rate of Clostridium difficile in healthy human adults is believed to be very low. Our RT‐PCR system using glass powder, which can eliminate PCR inhibitors, detected C. difficile toxin B mRNA in 16 of 30 fecal samples (53.3%) from healthy human adults. In contrast, we failed to detect toxin B in the same fecal samples by PCR using DNA templates extracted with phenol‐chloroform. Our results suggest that PCR inhibitors in feces carried through phenol‐chloroform extraction procedure might suppress the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
(3 reference statements)
1
5
0
1
Order By: Relevance
“…27,28 In at least 2 studies, the risk of colonization was shown to increase during hos pitalization, suggesting a cumulative daily risk of exposure to the healthcare environment. 25,29 Although 2 recent reports from Japan suggest that rates of carriage among asymptomatic adults without recent HCF exposure may be higher than pre viously thought, 30,31 these studies either involved culture of specimens from the same patient on multiple occasions, sug gesting transient colonization, 30 or involved the use of newly developed molecular methods that have not been similarly applied to patients in HCFs. 31 Historically, rates of carriage among asymptomatic adults without recent HCF exposure were found to be generally less than 2%.…”
Section: Appendix Rationale For Reporting Community-onset Hcf-associmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 In at least 2 studies, the risk of colonization was shown to increase during hos pitalization, suggesting a cumulative daily risk of exposure to the healthcare environment. 25,29 Although 2 recent reports from Japan suggest that rates of carriage among asymptomatic adults without recent HCF exposure may be higher than pre viously thought, 30,31 these studies either involved culture of specimens from the same patient on multiple occasions, sug gesting transient colonization, 30 or involved the use of newly developed molecular methods that have not been similarly applied to patients in HCFs. 31 Historically, rates of carriage among asymptomatic adults without recent HCF exposure were found to be generally less than 2%.…”
Section: Appendix Rationale For Reporting Community-onset Hcf-associmentioning
confidence: 99%
“…25,29 Although 2 recent reports from Japan suggest that rates of carriage among asymptomatic adults without recent HCF exposure may be higher than pre viously thought, 30,31 these studies either involved culture of specimens from the same patient on multiple occasions, sug gesting transient colonization, 30 or involved the use of newly developed molecular methods that have not been similarly applied to patients in HCFs. 31 Historically, rates of carriage among asymptomatic adults without recent HCF exposure were found to be generally less than 2%. 32,33 A recent study involving infants and very young children, in whom rates of asymptomatic carriage are known to be higher than in adults, 32 suggested that person-to-person transmission is re sponsible for carriage.…”
Section: Appendix Rationale For Reporting Community-onset Hcf-associmentioning
confidence: 99%
“…Recently introduced molecular methods, such as real-time PCR, have greater sensitivity than rapid toxin tests and thus are able to detect significantly more positive cases. However, these methods could also increase the detection of colonization in healthy people, up to 55.5% of which are colonized (3,7).…”
mentioning
confidence: 99%
“…This suggests that low-level endemic carriage of C. difficile is far more common than previously recognized. 26 Furthermore, most C. difficile recurrences (90%) appear to be attributed to endogenous C. difficile, 27 suggesting that it is not the presence of the organism that is problematic. Instead, it is the lack of other components of normal GI flora that predisposes individuals to developing CDAD.…”
Section: Cdad Preventionmentioning
confidence: 99%